Perceptions of Students on Industrial Training for Process and Food Engineering Program - Hasnan N.Z.N.; Yusoff Y.M. (American Institute of Physics Inc., 2023)
This paper present results of a study to investigate the perceptions of undergraduate students from the Process and Food Engineering Program on their industrial training. A total of 41 students (82%) were evaluated based on a questionnaire given to them once they have completed the 10-week internship. Over 80% of students perceived the industrial internship program positively in categories such as learning opportunity, relationship with colleagues, accessibility to supervisors and responsibilities assigned. Meanwhile, about 80% of students have a positive perception on the career development opportunities, level of challenges in the tasks, training sufficiency and integration of learnt theories into a real application. An interesting finding shows that the industrial training did not meet 36.6% students' expectation, as they perceived that the training provided was insufficient, limited opportunities to integrate engineering theories into practice and to involve in specific projects. Since the students have much to gain from industrial training, it becomes necessary for all stakeholders to collaboratively review and improve the training program based on duration, the context of their work tasks and career development aspects. This is to ensure that the program can effectively train the students to be job-ready and therefore, increase their employment prospects. 2022 American Institute of Physics Inc.. All rights reserved.